Double Diversification with an Application to Iceland - Thorvaldur Gylfason; Per Magnus Wijkman (Center for Economic Studies and ifo Institute (CESifo), 2015)
Excessive concentration increases national risk in an uncertain world. This paper views economic and political diversification as an essential aspect of national risk management aimed at promoting efficiency, growth, and welfare. The paper first presents economic and political diversification side by side in a cross-country framework and discusses how they interact and encourage more stable long-run economic growth. Thereafter, the paper considers Iceland as a case study of the intertwined effects of insufficient economic and insufficient political diversification. Dominated for decades by the fishing industry, the Icelandic economy is more diversified than before following the financial crisis of 2008 with tourism now generating more foreign exchange than fisheries. The paper ends with some general policy conclusions.
Keywords: F43; O13; O43; 330; diversification; concentration; democracy; Iceland